Towards intense single attosecond pulse generation from a 400 NM driving laser - Cheng, Yan (Kansas State University, 2011)
Attosecond pulse generation is a powerful tool to study electron dynamics in atoms and molecules. However, application of attosecond pulses is limited by the low photon flux of attosecond sources. Theoretical models predict that the harmonic efficiency scales as λ[lambda]-6 in the plateau region of the HHG spectrum, where λ [lambda] is the wavelength of the driving laser. This indicates the possibility of generating more intense attosecond pulses using short wavelength driving lasers. The purpose of this work is to find a method to generate intense single attosecond pulses using a 400 nm driving laser. In our experiments, 400 nm femtosecond laser pulses are used to generate high harmonics. First, the dependence of the high harmonic generation yield on the ellipticity of 400 nm driving laser pulse is studied experimentally, and it is compared with that of 800 nm driving lasers. A semi-classical theory is developed to explain the ellipticity dependence where the theoretical calculations match experiment results very well. Next, 400 nm short pulses (sub-10 fs) are produced with a hollow core fiber and chirped mirrors. Finally, we propose a scheme to extract single attosecond pulses with the Generalized Double Optical Gating (GDOG) method.
Keywords: Attosecond; High harmonic generation; Physics (0605)